Impact of empagliflozin on decongestion in acute heart failure: the EMPULSE trial : clinical research : clinical trials - Biegus, Jan; Voors, Adriaan A; Collins, Sean P; Kosiborod, Mikhail N; Teerlink, John R; Angermann, Christiane E; Tromp, Jasper; Ferreira, Joao Pedro; Nassif, Michael E; Psotka, Mitchell A; Brückmann, Martina; Salsali, Afshin; et al. (European heart journal, 2023)
Effective and safe decongestion remains a major goal for optimal management of patients with acute heart failure (AHF). The effects of the sodium-glucose cotransporter 2 inhibitor empagliflozin on decongestion-related endpoints in the EMPULSE trial (NCT0415775) were evaluated.A total of 530 patients hospitalized for AHF were randomized 1:1 to either empagliflozin 10 mg once daily or placebo for 90 days. The outcomes investigated were: weight loss (WL), WL adjusted for mean daily loop diuretic dose (WL-adjusted), area under the curve of change from baseline in N-terminal pro-B-type natriuretic peptide levels, hemoconcentration, and clinical congestion score after 15, 30, and 90 days of treatment. Compared with placebo, patients treated with empagliflozin demonstrated significantly greater reductions in all studied markers of decongestion at all time-points, adjusted mean differences (95% confidence interval) at Days 15, 30, and 90 were: for WL −1.97 (−2.86, −1.08), −1.74 (−2.73, −0.74); −1.53 (−2.75, −0.31) kg; for WL-adjusted: −2.31 (−3.77, −0.85), −2.79 (−5.03, −0.54), −3.18 (−6.08, −0.28) kg/40 mg furosemide i.v. or equivalent; respectively (all P < 0.05). Greater WL at Day 15 (i.e. above the median WL in the entire population) was associated with significantly higher probability for clinical benefit at Day 90 (hierarchical composite of all-cause death, heart failure events, and a 5-point or greater difference in Kansas City Cardiomyopathy Questionnaire total symptom score change from baseline to 90 days) with the win ratio of 1.75 (95% confidence interval 1.37, 2.23; P < 0.0001).Initiation of empagliflozin in patients hospitalized for AHF resulted in an early, effective and sustained decongestion which was associated with clinical benefit at Day 90.